PENINGKATAN KAPASITAS KUALITAS DAN PEMBERDAYAAN SUMBER DAYA MANUSIA DI DESA JATILUWIH - Utami, Ni Made Satya; Bhegawati, Desak Ayu Sriary; Skolastika, I Made Perdana (Publika Citra Media, 2024)
Jatiluwih, recognized as a UNESCO World Cultural Heritage site in 2012, attracts significant tourist attention. Despite its burgeoning development, the village faces challenges due to a lack of adequately trained human resources. Predominantly, educational attainment in the village is restricted to the secondary level, which limits management knowledge and skills among the residents. The Participatory Rural Appraisal (PRA) method, which involves engaging community groups in the examination of rural conditions, has been employed to address these challenges. This approach seeks to empower non-productive groups to enhance the overall capacity, knowledge, skills, and well-being of Jatiluwih's community, thereby fostering sustainable human resource development and improved socio-economic conditions.